Can Stronger Family Connections Alleviate the Adverse Effects of Unemployment on Happiness? Evidence from Asian Countries - Huang, Li-Hsuan (Journal of Reviews on Global Economics, 2018)
This study aims to investigate whether and how the family connection is critical to alleviate the negative effect of unemployment on people’s happiness by employing the World Values Survey data set regarding people in Chinese culture-related regions for empirical work. Empirically, we found family connections constitute a crucial factor in determining people’s happiness level. Except for living with parents, other family variables are positively significant in the happiness determination equation. Taking related measurements for family connections in the happiness determination equation is important in reducing estimation bias. Moreover, family connection reduces the fear of being unemployed and psychological losses from recession due to the worsening of job opportunities in economy. Stronger family connections can facilitate overcoming the stress and fear of being unemployed during recessions. Among the family-related variables, considering family important is of the largest marginal effect in alleviating the adverse effects of unemployment on happiness. This finding is robust among various age cohorts and between genders and among different model specifications. However, the ability of family connection to alleviate the adverse effect of unemployment on the happiness level of an unemployed worker is supported less by the data. We found that certain types of family connections might diminish the happiness of unemployed people, although the regression results are of no statistical significance. Those types of family connections include living with parents and considering family a crucial part of life.